Outcome of the Public Consultation on the draft statement of the PPR Panel on a framework for conducting the environmental exposure and risk assessment for transition metals when used as active substances in plant protection products (PPP). Issue 3 (29th March 2021) - ,; Pieper, Silvia; Aldrich, Annette; Berny, Philippe; Conrad, Arnaud; Padovani, Laura; Ippolito, Alessio; Kulikova, Olga; Lythgo, Chris; Egsmose, Mark
Abstract : EFSA performed a public consultation of the draft statement of the PPR Panel on a framework for conducting the environmental exposure and risk assessment for transition metals when used as active substances in plant protection products (PPP) from 3 August to 21 September 2020. EFSA was asked by the European Commission to prepare a public consultation on the draft statement. The statement provides a framework for conducting the environmental exposure, hazard characterisation and risk assessment for transition metals when used as active substances in plant protection products according to Regulation (EC) No 1107/2009 of the European Parliament and the Council. This report presents statistics on the comments received and answers to them. These comments were taken into account when finalising the statement. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2021.6498/full